Standing stockofThynnichthys thynnoideson dry seasonin the Lubuk Siam Lake, Siak Hulu district, Kampar regency - Amelia Amanda; Muhammad Fauzi; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Thynnichthys thynnoides is commonly inhabit the Lubuk Siam Lake.  A research aims to understandthe standing stock, relative growth rate, and recruitment pattern of the fish in the Lubuk Siam Lake was conducted in March 2018. Fish was sampled everyday for a week period, in 3 sampling points, using gillnets. The standing stock was analyzed using Leslie method, while relative growth rate and recruitment were analyzed using FISAT II softwae. Results shown that the standing stock of the fish was560 kg(L∞ 331.28 mm), K 0.430/year and t0-0.0174/year.Recruitment percentage in March is 2.03% and the highest predicted recruitment is in July (16.58%). Keywords : Leslie method, recruitment, growth rate, effort